PENINGKATAN pH TANAH MASAM DI LAHAN RAWA PASANG SURUT PADA BERBAGAI DOSIS KAPUR UNTUK BUDIDAYA KEDELAI - Danner Sagala (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2010)
The experiment was conducted at Taman Yasmin VI Bogor in June 2009. The Objective of this experiment was to know the effect of liming dosage on soil pH of Desa Banyu Urip. The experiment was laid on treatment of liming dosage that consisted of 1 ton/ha, 1.5 ton/ha, 2 ton/ha, 2.5 ton/ha and without liming as a comparison. The result showed that the liming dosage increased soil pH up to 5.36 for 2.5 ton/ha. It is strongly recommended to use 2.5 ton/ha of lime to improve the soil fertility in Desa Banyu Urip.